1976
DOI: 10.1002/1097-0142(197605)37:5<2359::aid-cncr2820370528>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Immature (malignant) teratoma of the ovary.A clinical and pathologic study of 58 cases

Abstract: Fifty-eight immature ovarian teratomas were studied. Neoplams with other germ cell elements (endodermal sinus tumor, choriocarcinoma, and dysgerminoma) were excluded so that the clinical and pathologic features of "pure" immature teratomas could be defined and correlated with the prognosis. The primary tumors and their metastatic growths were graded from 0 to 3. Forty were stage I; nine, stage II; and nine, stage III. The size and stage of teratomas were related to survival, but it was the grade of the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(87 citation statements)
references
References 10 publications
0
76
0
1
Order By: Relevance
“…The quantity of immature neural tissue alone determines the grade. [4] Therapy consists of unilateral salpingo-oophorectomy with wide sampling of peritoneal implants. If the tumor if confined to the ovary and grade I, no further therapy is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of immature neural tissue alone determines the grade. [4] Therapy consists of unilateral salpingo-oophorectomy with wide sampling of peritoneal implants. If the tumor if confined to the ovary and grade I, no further therapy is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Treatment with surgery followed by systemic chemotherapy can achieve remission and cure in over 90% of cases. [3, 4]…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal pain associated with a palpable abdominopelvic mass is observed in almost all patients. 13 Malignant ovarian germ cell tumours affect generally adolescent and young women with a peak incidence around 20years. 14 In the present study median age was 21 years and about 10% of patients were older than 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the 5-year overall survival rate for patients with immature teratoma of stage I and G1 was 98.5% if they underwent cystectomy without residual tumor. Norris et al reported that the rate of recurrence of immature teratoma was 18% in G1, 37% in G2, and 70% in G3, but the 5-year overall survival of patients with stage I and G1 tumors was 100% in 14 cases 13. Generally, immature teratoma patients of stage I and G1 are treated with surgery alone, because the prognosis is good.…”
Section: Discussionmentioning
confidence: 99%